Brain-targeting delivery of MMB4 DMS using carrier-free nanomedicine CRT-MMB4@MDZ - Yimeng Du; Jing Gao; Hui Zhang; Xiaohui Meng; Dong Qiu; Xiang Gao; Aiping Zheng (Taylor & Francis Group, 2021)
Brain-targeting delivery of 1,1'-methylenebis[4-[(hydroxyimino)methyl]-pyridinium] dimethanesulfonate (MMB4 DMS) is limited by its hydrophilic property and chemical instability. In order to solve this problem, herein, we develop a facile protocol through combining antisolvent precipitation and emulsion-solvent evaporation method to synthesize midazolam (MDZ) coated MMB4 DMS (MMB4@MDZ) nanoparticles. The as-prepared MMB4@MDZ had a MMB4 DMS nanocrystal (MMB4-NC) core and a MDZ shell. The MDZ shell prevented the MMB4-NC core from contacting the aqueous environment, and thus, guaranteed the chemical stability of MMB4 DMS. Most charmingly, the iron mimic cyclic peptide CRTIGPSVC (CRT) was modified on MMB4@MDZ surfaces to produce CRT-MMB4@MDZ which was endowed with ability to absorb transferrin (Tf)-abundant corona. Taking advantages of the Tf-abundant corona, CRT-MMB4@MDZ achieved transferrin receptor (TfR)-mediated brain-targeting delivery. With the fascinating chemical stability and brain-targeting delivery effect, CRT-MMB4@MDZ showed great clinical transform prospect as a brand-new nanomedicine. Of particular importance, this work promised not only a core-shell carrier-free nanomedicine platform for effective delivery of unstable water-soluble drug, but also a protein corona-manipulating strategy for targeting delivery.